2017
DOI: 10.3390/molecules22111811
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Bioactivity Evaluation of Novel β-carboline 1,3,4-oxadiazole Derivatives

Abstract: A series of novel β-carboline 1,3,4-oxadiazole derivatives were designed and synthesized, and the in vitro cytotoxic activity against Sf9 cells and growth inhibitory activity against Spodoptera litura were evaluated. Bioassay results showed that most of these compounds exhibited excellent in vitro cytotoxic activity. Especially, compound 37 displayed the best efficacy in vitro (IC50 = 3.93 μM), and was five-fold more potent than camptothecin (CPT) (IC50 = 18.95 μM). Moreover, compounds 5 and 37 could induce ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…The 2-thioxo-1,3,4-oxadiazole derivatives with special biological activities have attracted more and more attention and have been widely used in drug and pesticide molecular design in recent years [ 37 , 38 , 39 , 40 ]. Our previous study demonstrated that β-carboline 1,3,4-oxadiazoles which introduced the 2-thioxo-1,3,4-oxadiazole groups into β-carboline scaffolds at the C-3 position also exhibited significant cytotoxicity against Spodoptera frugiperda Sf9 cells [ 41 ]. In the present study, harmine and the novel ZC-14 bearing substituents in positions 1 and 3 of the β-carboline ring have been evaluated insecticides against Sf9 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-thioxo-1,3,4-oxadiazole derivatives with special biological activities have attracted more and more attention and have been widely used in drug and pesticide molecular design in recent years [ 37 , 38 , 39 , 40 ]. Our previous study demonstrated that β-carboline 1,3,4-oxadiazoles which introduced the 2-thioxo-1,3,4-oxadiazole groups into β-carboline scaffolds at the C-3 position also exhibited significant cytotoxicity against Spodoptera frugiperda Sf9 cells [ 41 ]. In the present study, harmine and the novel ZC-14 bearing substituents in positions 1 and 3 of the β-carboline ring have been evaluated insecticides against Sf9 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Harmine was purchased from Sigma (Santa clara, CA, USA) and the derivative ZC-14 [1-(2-naphthyl)-3-(2-thioxo-1,3,4-oxadiazol-5-yl) β-carboline] was synthesized in our lab ( Figure 1 ). ZC-14 was synthesized using harmine as the lead compound and position 1 replaced with naphthalen and position 3 replaced by 2-thioxo-1,3,4-oxadiazole group [ 41 ]. Dimethyl sulfoxide (DMSO) of analytical reagent purchased from Sigma was used as the solvent for dissolving harmine and ZC-14.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, rearrangment of this intermediate in various alcohols yielded the substituted indole-2-carbamates 15 -18 [20]. Compound 19 was prepared according to our previously reported procedure [21]. N-benzylation of indole was accomplished using 2-chloro-5-chloromethylpyridine in the presence of sodium hydride, furnishing 1-(6-chloro-3pyridylmethyl)-1H-indole 28.…”
Section: Chemistrymentioning
confidence: 99%
“…Of these compounds, indole (7, EC 50 = 25.56 µg/mL) displayed superior fungicidal activity, and was 7-fold as potent as validamycin A (EC 50 = 183.00 µg/mL). Additionally, it can be seen quite clearly that the structural changes in general were detrimental to activity and no favorable substitution could be found for the 2-or 3-position, even after extensive probing with a variety of diverse groups (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). These findings implied that indole was a potent fungicidal template for further modification and derivatization.…”
Section: Chemistrymentioning
confidence: 99%
“…The reported biological applications of β-carboline alkaloids include sedative and anxiolytic [ 6 ], antitumor [ 7 , 8 ], antimalarial [ 8 ], antiparasitic [ 9 ], anti-HIV [ 10 ] agents, and other pharmacological activities. As for pest management, the extracts of Peganum harmala L. plant species containing a mixture of harmine, harmaline, and norharman, as well as their derivatives, had been proven to have excellent insecticidal, fungicidal, and plant growth regulatory properties [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In our previous work [ 18 ], we found that 9-fluorosubstituted-harmine displayed higher fungicidal activities against Rhizoctonia solani , Rape sclerotinia rot, and Alternaria kikuchiana Tanaka.…”
Section: Introductionmentioning
confidence: 99%